Social Work Activities Supporting Patients at Hospitals in Nghe An, Vietnam - Le, Thi Kim Dung; Nguyen, Thi Hoai An (Asean Social Work Journal, 2025)
Hospital social work in Vietnam has been introduced to support patients, yet faces substantial challenges and has not achieved its intended outcomes. This study, based on quantitative surveys with 500 patients and 255 healthcare professionals, alongside in-depth interviews across five hospitals in Nghe An province, provides a comprehensive overview of current practices. Findings show that social work activities—such as patient reception, information provision, psychosocial support, discharge assistance, and emergency response—are aligned with patient needs and implemented in accordance with Circular No. 43/2015. However, these tasks are often carried out by both social workers and healthcare staff, and remain largely administrative. Key barriers include a shortage of trained professionals, fragmented operational mechanisms, and limited institutional recognition of social work’s role in healthcare. The study recommends strengthening legal frameworks, enhancing workforce capacity, and raising awareness of the professional functions of hospital social workers.